Perlindungan Hukum Bagi Pembeli Perumahan Syariah Tanpa Melalui Lembaga Keuangan di Masa Pandemi COVID-19 - Novenry, Yudiet; Hamidah, Siti; Sukarmi, Sukarmi (Universitas Negeri Malang, 2022)
This study aimed to discuss legal protection for buyers in Islamic housing with istishna contracts during the COVID-19 pandemic and developers' efforts to overcome the problem of late payments. The study method used empirical juridical with qualitative descriptive analysis methods. The istishna contract had not provided legal protection because the agreement's substance was the developer's absolute right, so the buyer could not change it. Instead, the developer did three things to overcome delays in fulfilling the buyer's instalment obligations: explaining the istishna contract, delaying payment, and carrying out joint selling if the buyer could not pay instalments or pay them off.